Plagued by a cryptic clock: insight and issues from the global phylogeny of Yersinia pestis - Katherine Eaton; Leo Featherstone; Sebastian Duchene; Ann G. Carmichael; Nükhet Varlık; G. Brian Golding; Edward C. Holmes; Hendrik N. Poinar (Communications Biology, 2023)
The emergence of the plague pathogen throughout history is investigated using molecular clock modelling and phylogenetic analyses.